2021
DOI: 10.1101/2021.06.03.446796
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ring Finger Protein 213 Assembles into a Sensor for ISGylated Proteins with Antimicrobial Activity

Abstract: ISG15 is an interferon-stimulated, ubiquitin-like protein that can conjugate to substrate proteins (ISGylation) to counteract microbial infection, but the underlying mechanisms remain elusive. Here, we used a viral-like particle trapping technology to identify ISG15-binding proteins and discovered Ring Finger Protein 213 (RNF213) as an ISG15 interactor and cellular sensor of ISGylated proteins. RNF213 is a poorly-characterized, interferon-induced megaprotein that is frequently mutated in Moyamoya disease, a ra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 97 publications
1
7
0
Order By: Relevance
“…Conversely, among potential anti-viral factors, we found IFI16, which was previously characterized as anti-viral in immediate early and pro-viral in later stages of HCMV infection 21 . Other anti-viral candidates not described yet in the context of HCMV infected moDCs included the broadly anti-viral ISG15 interactor RNF213 22 and TNFSF10 encoding the NK cell-activating protein TRAIL 44,45 . Since NK cells critically contribute to anti-HCMV immunity and HCMV-encoded UL141 is known to block TRAIL receptors 46 , the particularly strong downregulation of TRAIL expression early upon infection that we observed here is likely another mechanism to escape NK cell-mediated killing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, among potential anti-viral factors, we found IFI16, which was previously characterized as anti-viral in immediate early and pro-viral in later stages of HCMV infection 21 . Other anti-viral candidates not described yet in the context of HCMV infected moDCs included the broadly anti-viral ISG15 interactor RNF213 22 and TNFSF10 encoding the NK cell-activating protein TRAIL 44,45 . Since NK cells critically contribute to anti-HCMV immunity and HCMV-encoded UL141 is known to block TRAIL receptors 46 , the particularly strong downregulation of TRAIL expression early upon infection that we observed here is likely another mechanism to escape NK cell-mediated killing.…”
Section: Discussionmentioning
confidence: 99%
“…5b). Indeed, we identi ed three ISGs as the most negatively correlated host genes in P, including (i) IFI16 that was previously reported to be a restriction factor of early HCMV infection 21 , (ii) RNF213, an ISG15 interactor 22 ), and (iii) TNFSF10 (TRAIL), the latter two of which so far have not been recognized to directly affect HCMV replication.…”
Section: Increased Expression Of Viral Rnas Is Associated With Downregulation Of Interferon Stimulated Genes and Upregulation Of Heat Shomentioning
confidence: 99%
“…However, RNF213-mediated immune response might not be limited to the gram-negative bacterium Salmonella. A recent study suggested that RNF213 exerts a much broader antimicrobial activity, counteracting infections with the gram-positive bacterium L. monocytogenes as well as several viral pathogens in vitro (preprint: Thery et al, 2021). Importantly, this finding would imply that LPS is unlikely the only target of RNF213 and other substrates might exist.…”
Section: Rnf213mentioning
confidence: 99%
“…Molecular Cell 81, July 1, 2021 2691 ll that it can target (Thery et al, 2021). As with ester-linked modifications, however, appreciating the full extent to which lipids may be ubiquitinated in cells awaits new methodologies.…”
Section: Spotlightmentioning
confidence: 99%
“…A unique O-antigen coat used by the intracellular pathogen Francisella tularensis, for example, has been shown to shield the bacterium from ubiquitination and resulting xenophagy (Case et al, 2014). Remarkably, although the Gram-positive-and therefore LPS-lacking-pathogen Listeria monocytogenes has been shown to escape ubiquitination using actin-based motility, recent work from the Impens laboratory shows that RNF213 still localizes to and restricts the growth of intracellular Listeria in a manner that requires the E3 ligase module, suggesting that RNF213 may have a related ligase-dependent but LPS-independent role in responding to ll Gram-positive bacterial infection (Thery et al, 2021). Whether and how RNF213 responds to and ubiquitinates other invading bacteria will be an interesting future direction with broader implications on cell-autonomous immunity.…”
mentioning
confidence: 99%